2018
DOI: 10.1371/journal.pone.0201165
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between different elements of reported burden and common mental disorder in caregivers of ethnically diverse people with dementia in Trinidad

Abstract: ObjectiveCulture plays a significant role in determining family responsibilities and possibly influences the caregiver burden associated with providing care for a relative with dementia. This study was carried out to determine the elements of caregiver burden in Trinidadians regarding which interventions will provide the most benefit.MethodsSeventy-five caregivers of patients diagnosed with dementia participated in this investigation. Demographic data were recorded for each caregiver and patient. Caregiver bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Ethnical and contextual influence are widely recognised to be associated with burnout, but investigation using a representative sample is limited. Ethnicity and social structure are important factors contributing to the difference in dementia caregiving experience [ 16 18 ]. For example, African American dementia caregivers were found to have better wellbeing comparing to their white counterparts [ 19 ]; while dementia caregivers in Korea is more burdened than Korean-American and white caregivers [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnical and contextual influence are widely recognised to be associated with burnout, but investigation using a representative sample is limited. Ethnicity and social structure are important factors contributing to the difference in dementia caregiving experience [ 16 18 ]. For example, African American dementia caregivers were found to have better wellbeing comparing to their white counterparts [ 19 ]; while dementia caregivers in Korea is more burdened than Korean-American and white caregivers [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used the GHQ12-J, which has been used in previous studies (Perlick et al, 2013;Sakanashi & Fujita, 2017a). However, previous studies have reported that the GHQ is related to caregiver burden (using the Zarit Burden Interview, ZBI; Baboolal, Davis, Stewart, Ramesar, & McRae, 2018) and psychological distress of family caregivers (using the Neuropsychiatry Inventory, NPI, and Perceived Stress Scale, PSS; Javadpour, Ahmadzadeh, & Bahredar, 2009). The GHQ tends to focus on negative concepts, so the use of the GHQ12-J may constitute weak evidence for the criterion validity of the EFCD, as we believe that the EFCD reflects more positive concepts such as self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding race/skin colour, White caregivers had higher levels of burden in six studies compared to Black caregivers (Cothran et al, 2017;Fredman et al, 1995;Martin, 2000;Skarupski et al, 2009;Spurlock, 2005) and Latin caregivers (Montoro-Rodriguez & Gallagher-Thompson, 2009). Other studies found that Hispanic caregivers had higher levels of burden compared to Black caregivers (Cox & Monk, 1996) and Black caregivers had higher levels of burden compared to Indian caregivers (Baboolal et al, 2018).…”
Section: Caregiver Characteristicsmentioning
confidence: 96%
“…Thailand, India, Turkey, Mexico and China (Akpınar et al, 2011;Baboolal et al, 2018;Chan & Chui, 2011;Chindaprasirt et al, 2014;Gok Metin et al, 2019;Zhan, 2002Zhan, , 2005 and another seven were carried out in more than one developed and developing country (Chan et al, 2021;Chun et al, 2007;Konerding et al, 2019;Losada et al, 2006;Smith et al, 2019;Sousa et al, 2016;Youn et al, 1999). The United States accounted for the largest number of studies (n = 16).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%